A Fully Printable Strain Sensor Enabling Highly‐Sensitive Wireless Near‐Field Interrogation - Hassan A. Mahmoud; Hussein Nesser; Tarek M. Mostafa; Shehab Ahmed; G. Lubineau (Advanced Science, 2025)
Abstract Wireless, passive, and flexible strain sensors can transform structural health monitoring across various applications by eliminating the need for wired connections and active power sources. Such sensors offer the dual benefits of operational simplicity and high‐function adaptability. Herein, a novel wireless sensor is fabricated using radio frequency (RF) technology for passive, wireless measurement of mechanical strains. Previously introduced concept of coupling piezoresistive electrodes is utilized with capacitive sensors to ensure high‐sensitivity capacitive sensing. For the first time, it is implemented and demonstrated here as a fully printable, inexpensive, and ready‐to‐use device utilizing the recent advances in piezoresistive inks and screen‐printing technologies. The near‐field communication (NFC) tag features an inductor ‐ capacitor (LC) resonant circuit with a distinct resonant frequency. The sensor exhibits high sensitivity and detects substantial variations in capacitance, with a gauge factor (GF) of ≈16 at 20 MHz for strain levels below 5%. Within the wireless framework, the sensor achieves a significant shift in resonance frequency (GF of ≈2.2). It also exhibited excellent performance in wirelessly monitoring the strain in a glass fiber‐reinforced polymer (GFRP) specimen during the bending test. The results confirm the potential applicability of the sensor as an embedded sensor for monitoring various types of composite structures. This confirms the potential of the sensor for use in composite structures as an embedded sensor.